2012
DOI: 10.5740/jaoacint.11-178
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Pomegranate Juice

Abstract: A database of 793 commercial pomegranate juices was analyzed to produce a profile for authentication of pure pomegranate juice. The database consisted of data from a mix of authentic and adulterated samples. Statistical tools were used to reduce the database to a stable sample set of 477 presumably authentic samples. The profile obtained (mean, SD at 16 Brix) are as follows: fructose (g/100 g) 6.83, 0.50; glucose (g/100 g) 6.66, 0.44; sucrose (g/100 g) 0.00, 0.00; sorbitol (g/100 g) 0.00, 0.01; acidity (g/100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 0 publications
3
48
0
2
Order By: Relevance
“…Terdapatnya pengaruh yang nyata tingkat yogurt terhadap kecernaan bahan kering, bahan organik, dan protein kasar diduga karena kandungan glukosa dalam kulit nanas (Krueger et al, 1992;Raji et al, 2012) yang merupakan non struktural karbohidrat siap dicerna menjadi sumber energi bagi mikrobia rumen (Bailey et al, 2012) sehingga mikrobia rumen meningkat pertumbuhan dan keaktifannya. Mikrobia yang terkandung dalam cairan rumen diantaranya adalah bakteri proteolitik, bakteri yang menghasilkan enzim protease.…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…Terdapatnya pengaruh yang nyata tingkat yogurt terhadap kecernaan bahan kering, bahan organik, dan protein kasar diduga karena kandungan glukosa dalam kulit nanas (Krueger et al, 1992;Raji et al, 2012) yang merupakan non struktural karbohidrat siap dicerna menjadi sumber energi bagi mikrobia rumen (Bailey et al, 2012) sehingga mikrobia rumen meningkat pertumbuhan dan keaktifannya. Mikrobia yang terkandung dalam cairan rumen diantaranya adalah bakteri proteolitik, bakteri yang menghasilkan enzim protease.…”
Section: Hasil Dan Pembahasanunclassified
“…Sruamsiri (2007) melaporkan bahwa kulit nanas mengandung karbohidrat tinggi yang merupakan karbohidrat terlarut dan mudah terdegradasi sebagai sumber energi serta mengandung enzim bromelin yang berguna untuk metabolisme protein. Krueger et al (1992) menyatakan bahwa kulit nanas mengandung sukrosa, fruktosa, glukosa, dan zat makanan lainnya. Disamping potensinya, penggunaan kulit nanas sebagai bahan pakan ternak terutama untuk ternak unggas terkendala dengan kualitasnya yang rendah dan cepat rusak atau mengalami pembusukan akibat kandungan air yang cukup tinggi.…”
unclassified
“…The major elemental components present in pineapple fruits are K, Ca, Mg and P [9]. Al, Fe, Na and Zn are present in trace amount but Pb was not detected in pineapple fruits.…”
Section: Mineral Characteristicsmentioning
confidence: 99%
“…The reducing sugar content, which was identical between the three types of pineapple fruits, seems to reveal that the sweetened nature of fruits FE and FM is related to the presence of no reducing sugars. Indeed, Krueger and Krueger [9] reported that glucose and the fructose have smaller proportions in natural pineapples juices compared to sucrose, and Hodgson and Hodgson [10] revealed that sucrose is the main sugar in pineapple fruit. Amino acid and total proteins content of fruits FM and FE were higher than those of fruits FR (Table 3).…”
Section: Biochemical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation